A comparison of shot selection and goal scoring between collegiate and professional women`s and men`s ice hockey - Csiernik, B.; Cavell, M.; Nauboris, K.; Wattie, N. (Frontiers in Sports and Active Living, 2025)
The purpose of this study was to examine the differences and similarities in shooting and scoring trends between collegiate women's hockey, and professional men's and women's hockey. A multinomial logistic regression using shot data from the Ontario University Athletics women's hockey league, Professional Women's Hockey League, and the National Hockey League revealed statistically significant differences, indicating that each league has unique shooting patterns. Understanding that each league has different shooting and scoring profiles is relevant to coaches, who may benefit from using normative data from their own leagues to support decision making, rather than results from other leagues.